Impact of transcutaneous auricular vagus nerve stimulation (taVNS) on cognitive flexibility as a function of task complexity - Mena-Chamorro, Patricio; Espinoza-Palavicino, Tomás; Barramuño-Medina, Mauricio; Romero-Arias, Tatiana; Gálvez-García, Germán (Frontiers in Human Neuroscience, 2025)
PurposeThis study aimed to evaluate the effect of transcutaneous auricular vagus nerve stimulation (taVNS) on cognitive flexibility under different levels of task complexity. The hypothesis was that taVNS would enhance cognitive flexibility more effectively under demanding task conditions.MethodA within-subject design was used, involving 24 healthy adults who completed a Dimensional Change Card Sorting task combined with an auditory task of varying difficulty levels (low, medium, high). Participants underwent both active and sham taVNS conditions while performing the tasks. The complexity of the auditory task served to reduce cognitive resources available for the cognitive flexibility task, allowing an assessment of how taVNS modulates cognitive flexibility under different task difficulty conditions.ResultsThe results show that switch costs in the Dimensional Change Card Sorting task increase with task difficulty. In addition, active taVNS reduced switch costs significantly in the high complexity condition, while no differences were observed in the low and medium complexity conditions. This indicates that taVNS is particularly effective in conditions of higher cognitive demand.ConclusionThe findings suggest that taVNS enhances cognitive flexibility, especially in more complex tasks, providing a better understanding of the effects of taVNS on cognitive control.